SEF/IL-17R (SEFIR) Is Not Enough: AN EXTENDED SEFIR DOMAIN IS REQUIRED FOR IL-17RA-MEDIATED SIGNAL TRANSDUCTION - Onishi, Reiko M. (American Society for Biochemistry and Molecular Biology, 2010)
IL-17, the hallmark cytokine of the Th17 population, mediates immunity to extracellular pathogens and promotes autoimmune immunopathology. The signaling mechanisms triggered by the IL-17 receptor (IL-17RA) and related receptors are strikingly different from other cytokine subclasses. Namely, IL-17Rs contain a conserved SEF/IL-17R (SEFIR) subdomain that engages Act1, leading to activation of TRAF6, NF-κB, and other events. Although the SEFIR is critical for signaling, the molecular details of the functional subdomains within IL-17RA remain poorly characterized. Here, we provide a detailed structure-function analysis delineating the C-terminal boundary of the SEFIR-containing region of IL-17RA. We show that functionality of this domain requires a large extension to the previously identified SEFIR motif. In contrast to the SEFIR, this extension is not conserved among IL-17R family members. Surprisingly, Act1 recruitment is not sufficient for downstream signaling activation, whereas ubiquitination of TRAF6 correlates tightly with functional receptors. We further demonstrate that IL-17RA exhibits signaling properties that are nonredundant with other IL-17R family members. Finally, we report that IL-17 signals synergistically with lymphotoxin-α3, using the same signaling motifs within IL-17RA. These studies provide new insight into the structure-function relationships of IL-17RA and reveal distinct signaling differences among IL-17R family members.